2018
DOI: 10.15740/has/ijas/14.1/149-153
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of boron, urea and GA3 influences earliness of curd production in broccoli (Brassica oleracea var. italica)

Abstract: Broccoli (Brassica oleracea var. italica) which belongs to Brassicaceae family, is an Italian vegetable, native to Mediterranean region. Although broccoli is not so popular yet in Jharkhand, it is slowly gaining popularity during the last few years among the consumers due to its nutritional value including flavour, taste, carotenoids and anticancerous properties. Among the entire cole family, broccoli is rated as most remunerative. To assess the impact of foliar spray of boron, Urea and GA 3 on earliness in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This is in agreement with the results obtained by Patil et al (1987). Verma et al (2018) reported the minimum days (56.33 days) required to head formation when GA3 @ 75 ppm was sprayed followed by GA3 @ 50 ppm (58.51 days). 4.87 -T0 = Distilled water (control), T1 = GA3 @ 20 ppm, T2 = GA3 @ 40 ppm, T3 = GA3 @ 60 ppm, T4 = GA3 @ 80 ppm, T5 = GA3 @ 100 ppm; Y1 = 2014-15, Y2 = 2015-16; ns = not significant.…”
Section: Effect Of Ga3 On Growth Charactersmentioning
confidence: 99%
“…This is in agreement with the results obtained by Patil et al (1987). Verma et al (2018) reported the minimum days (56.33 days) required to head formation when GA3 @ 75 ppm was sprayed followed by GA3 @ 50 ppm (58.51 days). 4.87 -T0 = Distilled water (control), T1 = GA3 @ 20 ppm, T2 = GA3 @ 40 ppm, T3 = GA3 @ 60 ppm, T4 = GA3 @ 80 ppm, T5 = GA3 @ 100 ppm; Y1 = 2014-15, Y2 = 2015-16; ns = not significant.…”
Section: Effect Of Ga3 On Growth Charactersmentioning
confidence: 99%